Uncovering the evolving drivers of student engagement in physical education: a dynamic analysis across developmental stages - Lv, Zeren (Frontiers in Psychology, 2026)
PurposeTo address the limitations of static and subjective methods, this study aims to examine the dynamic interplay among factors influencing student engagement in physical education across different developmental stages.MethodThis study integrates an enhanced Delphi method with a Time-Varying Influence Network model and dynamic MICMAC analysis to compute time-varying driver power and dependency from the evolving total influence matrix.ResultsThe dynamic system evolution was characterized by three key patterns: convergence toward equilibrium, transient dominance, and structural stability.Discussion/conclusionThe dynamic system evolution is characterized by three key patterns: convergence toward equilibrium, transient dominance, and structural stability. These results underscore the importance of timing and targeting in intervention strategies and the need to reinforce stable core elements.